2014
DOI: 10.1080/15298868.2014.889033
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulatory Responses to Unattainable Goals: The Role of Goal Motives

Abstract: Does motivation for goal pursuit predict how individuals will respond when confronted with unattainable goals? Two studies examined the role of autonomous and controlled motives when pursuing an unattainable goal without (Study 1) or with (Study 2) the opportunity to reengage in alternative goal pursuit. Autonomous motives positively predicted the cognitive ease of reengagement with an alternative goal when the current goal was perceived as unattainable, especially when participants realized goal unattainabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 35 publications
2
55
1
Order By: Relevance
“…Research from self-determination theory also indicates that motivation plays a key role in disengagement -although it may be difficult to disengage from an unattainable goal, people may be better off disengaging earlier on rather than trying to stick it out, especially in the case of pursuing a goal that is tied to one's sense of self (i.e., an autonomous goal) (Ntoumanis, Healy, Sedikides, Smith, & Duda, 2014).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Research from self-determination theory also indicates that motivation plays a key role in disengagement -although it may be difficult to disengage from an unattainable goal, people may be better off disengaging earlier on rather than trying to stick it out, especially in the case of pursuing a goal that is tied to one's sense of self (i.e., an autonomous goal) (Ntoumanis, Healy, Sedikides, Smith, & Duda, 2014).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Alternately, in an ego-oriented motivational climate, focus is placed upon the specific indicators of competition and athletic performance. Numerous studies have been completed using this construct (Duda, Chi, Newton, Walling, and Catley, 1995;Duda and Nicholls, 1992;Jiménez, 2004;Newton and Duda, 1993;Ntoumanis, Healy, Sedikides, Smith, and Duda, 2014) with the general conclusions indicating a stronger association between boys and an ego-oriented motivational climate, and girls showing a greater tendency toward a motivational climate task-oriented.…”
Section: Introductionmentioning
confidence: 99%
“…Differently, a possible explanation for our finding is that although high levels of self‐confidence are considered adaptive for adolescent development, some problems may arise if high levels of self‐confidence lead adolescents to pursue exceedingly unrealistic goals that they are unable to reach. Previous research has reported that striving for goals that are out of reach without adopting goal disengagement strategies can set the stage for a chronic failure to reach one's goals, which in turn may lead one to experience negative affects and enhanced levels of psychological distress (Ntoumanis, Healy, Sedikides, Smith, & Duda, ). Finally, the present study showed that higher degrees of openness to sexuality and sexual experiences were associated with greater impairment in psychosocial functioning.…”
Section: Discussionmentioning
confidence: 99%